ANALYSIS OF INDONESIAN LANGUAGE USAGE ON SIGNBOARDS TOURIST ATTRACTIONS AND ROADS IN CENTRAL MALUKU REGENCY - Wa Mirna; Nur Apriani Nukuhaly; Rahma Anugraheny; Adi Setiawan; Agik Nur Efendi (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
The use of proper and correct Indonesian on public signage reflects professionalism and the image of a region in the eyes of tourists and the general public. This study aims to analyze the use of Indonesian on tourism signage and street signs in Central Maluku Regency. This research uses a qualitative method with a phenomenological approach to reveal the reality of Indonesian language usage in public spaces. The findings of this study include two main results. First, the portrayal of Indonesian usage on tourism signage and street signs in the areas of Tulehu, Waai, Liang, and Morella, which contains 16 data points (10 tourism signage data and 6 street sign data). These are only three tourism signs (in Tulehu, Liang, and Morella) adhered to normative theory, while the rest did not, especially those in Wai, Liang, Tulehu, and Morella. Second, there are four areas where the signs align with communicative theory (Tulehu, Waai, Liang); however, two data points in Tulehu and Morella do not align due to incorrect writing on street signs, which causes confusion among road users. This study makes a significant contribution to the development of language policy, particularly in organizing Indonesian language in public spaces in Central Maluku Regency. The results can serve as a reference for local governments, tourism destination managers, and the public to raise awareness and skills in using proper and correct Indonesian, thus creating a positive regional image and facilitating public communication